Increased IL-31 expression in serum and tissue protein in prurigo nodularis - Suteeraporn Chaowattanapanit; Rachot Wongjirattikarn; Nipon Chaisuriya; Piti Ungarreevittaya; Pirawan Poosekeaw; Kengkart Winaikosol; Charoen Choonhakarn; Narachai Julanon; Kanin Salao (SAGE Publishing, 2022)
Background: Prurigo nodularis (PN) is a chronic pruritic skin disease which can greatly impact patients' quality of life. Moreover, the pathogenesis remains unclear, making it a difficult-to-treat condition. Aims: To investigate the expression of interleukin-31 (IL-31) in serum and skin biopsy specimens of PN patients and healthy subjects and identify its possible correlation to disease severity and itch intensity. Methods: Patients with PN and healthy volunteers were recruited for the study. Expression levels of IL-31 were measured by enzyme-linked immunosorbent assay and immunohistochemistry. Baseline characteristics, disease activity, itch intensity, and related laboratory results were collected. Results: Forty-three PN patients and 31 healthy subjects participated in our study. The PN patients had significantly higher mean serum IL-31 levels than the healthy subjects (52.9 ± 18.2 versus 36.3 ± 10.7 pg/ml, p  < 0.001). Epidermal and dermal PN lesions also exhibited significantly higher IL-31 expression compared with the healthy skin ( p  < 0.001 and p  = 0.01, respectively). However, there was no significant difference in serum or lesional expression of IL-31 by disease severity or itch intensity. Conclusion: Increased IL-31 expression in serum and PN lesions suggests that IL-31 has a potential role in the pathogenesis of PN.